EXAMINING THE POTENTIAL CONSEQUENCES OF GENDER EQUALITY ISSUES AMONG STUDENT YOUTH - Xaydarova Sayyora (American Journals, 2024)
Gender equality is a fundamental principle that promotes fairness and equal opportunities for individuals of all genders. However, there are certain potential consequences associated with gender equality issues among student youth that need to be addressed. This article explores the dangerous consequences that can arise when gender equality is not effectively addressed in educational settings. It examines the impact on mental health, social dynamics, academic performance, and future career prospects. The article emphasizes the importance of fostering a gender-inclusive environment and provides recommendations for promoting gender equality to mitigate these potential consequences. By addressing gender equality issues among student youth, educational institutions can create a safe and supportive environment that benefits all students.
Keywords: Gender equality, student youth, consequences, mental health, social dynamics, academic performance, career prospects.